2022
DOI: 10.1002/jcu.23326
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research progress of myocardial work in assessment and prediction of coronary artery disease in noninvasive pressure‐strain loop technique

Abstract: Early identification and treatment of high‐risk coronary artery disease (CAD) is the main goal of current cardiovascular disease treatments. Speckle‐tracking ultrasound technology can quantify myocardial work using pressure‐strain loops. Because myocardial work takes into account the effect of the left ventricular systolic function afterload, it can more objectively reflect left ventricular myocardial mechanical function than the overall left ventricular longitudinal strain. Therefore, this technique is more w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…Myocardial work parameters often provides more information compared with GLS, which can be said to be a further complement to GLS. [24] In the final statistical process, we found that there were indeed a number of cases in which the dysfunctional myocardium could not be identified by GLS alone, which most likely due to the limitations of 2D-STE. It only considered the length change of the myocardium during the entire cardiac cycle, without taking into account the load changing, which makes myocardial work analysis more sensitive than GLS to identify the region of dysfunctional myocardium.…”
Section: Discussionmentioning
confidence: 87%
“…Myocardial work parameters often provides more information compared with GLS, which can be said to be a further complement to GLS. [24] In the final statistical process, we found that there were indeed a number of cases in which the dysfunctional myocardium could not be identified by GLS alone, which most likely due to the limitations of 2D-STE. It only considered the length change of the myocardium during the entire cardiac cycle, without taking into account the load changing, which makes myocardial work analysis more sensitive than GLS to identify the region of dysfunctional myocardium.…”
Section: Discussionmentioning
confidence: 87%
“…Noninvasive PSL have been previously validated as a surrogate of MW and overcome the load‐dependency of EF and LS. Indeed, MW takes into account deformation as well as afterload through interpretation of strain in relation to noninvasive LV pressure (estimated by measurement of cuff pressures) 19,40–42 . Assessments of MW were already done in preclinical and adult cohorts of patients 21,22,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MW takes into account deformation as well as afterload through interpretation of strain in relation to noninvasive LV pressure (estimated by measurement of cuff pressures). 19,[40][41][42] Assessments of MW were already done in preclinical and adult cohorts patients. 21,22,43 For example, MW has been assessed in ischemic cardiac disease, allowing the detection of subclinical coronary artery disease without any regional wall motion abnormalities, and has more sensitivity for myocardial oxygen consumption.…”
Section: Lower Mw In Cls Especially On Apical Segmentsmentioning
confidence: 99%
“…About 1/3 of the patients may have sensorineural hearing loss. The clinical features of patients with FEVR are mild and do not present with any symptoms, and the peripheral vascular zone of the retina is visible during screening [20] . In severe cases, secondary neovascularization, retinal folds and exudations, and tractional retinal detachment can be observed.…”
Section: Discussionmentioning
confidence: 99%